Biology, Control and Invasive Potential of Giant Reed (Arundo donax L.) in Florida - Patrick Minogue; Seth Wright (EDIS)
Arundo donax (L.), also known as giant reed, is a tall, fast-growing, bamboo-like grass that under ideal conditions can reach a height of up to 30 feet and a stem diameter up to 1.5 inches. Giant reed is invasive and difficult to control and has caused economic losses in California, Nevada, Utah, Arizona, New Mexico, and Texas. This species was introduced to Florida over 100 years ago and is currently naturalized in at least 26 of the 67 Florida counties. So far, giant reed has not proved problematic in Florida, but recent permitting of its planting for bioenergy feed stock may increase the risk that it could naturalize into plant communities in Florida and other southeastern states and potentially cause economic losses as well as harm to native species and habitats. This 5-page fact sheet describes the biology of this species and explains some strategies for its control. Written by Pat Minogue and Seth Wright and published by the School of Forest Resources and Conservation, March 2016.